Physiological, biochemical and molecular analyses of fruit development in oil palm (Elaeis guineensis Jacq.) - Abdul Wahab, Nurniwalis (2017)
In Malaysia, oil palm is the main commodity crop and has strongly contributed to the country’s economic development. However, the industry is facing several challenges including diminishing land resource for expansion. One of the targets to ensure oil palm sustainability is to increase yield per unit area without affecting its quality and with minimal impact to the environment. The non-synchronized ripening process and shedding of the fruits is among the factors that limit yield improvement and affect oil quality. Thus, the present study was conducted to deepen our understanding of the changes that occur within the fresh fruit bunch (FFB) during fruit development. This work also takes into account the various fruit positions (inner, middle and outer) and locations (apical, central and basal) within the bunch.